The Workforce in Indonesian Organizations: An Analysis Based Upon the Cultural Dimensions of Hofstede’s Model - Bella Santya Artina; Dita Desnasari; Fita Fitriyah; Rainda Goesti Rizkita (Journal of International Conference Proceedings (JICP), 2020)
Culture has been understood as one of the factors that has a strong component in influencing all management activities. This study was aimed to study the role of six cultural dimensions of Hofstede’s model and its impact on the workforce in Indonesian organizations. This study is qualitative research and using the metaanalysis method. Indonesia has a high power distance and collectivism, moderately in masculine, low preference for avoiding uncertainty, long-term oriented, and restraint which has an impact on the workforce. Results of this study showed that practical understanding of cultural dimensions of Hofstede’s model and its impact on the workforce in Indonesian organizations.